Harmonizing the religion, arts, and culture: Value of compassion as a conflict resolver in Sumedang - Hilman Taufiq Abdillah; Syahidin Syahidin (Universitas Pendidikan Indonesia, 2025)
Sumedang Regency faces a sociological challenge in the form of a sharp dichotomy between puritanical religious practices and local cultural arts expressions. This phenomenon hinders the optimization of social capital in building community character. This article aims to deconstruct the roots of this dichotomous conflict and reconstruct a new synergy model based on the Grand Theory of the integration of religion, arts, and culture, with the value of